Study of histological and epidemiological parameters associated with tumor size of canine neoplasms (Research, Society and Development, 2022)
Mammary neoplasms are increasingly frequent oncological disorders in canines and one of the characteristics most related to clinical prognosis is tumor size. Thus, the objective of this study was to evaluate different histological parameters (tumor type and degree of malignancy) and epidemiological parameters (age, race, contraceptive use and reproductive status) and to relate them to the tumor size of canine mammary neoplasms received between 2016 and 2016. to 2021 at the Veterinary Oncology Service of the Federal University of Pelotas. A total of 1549 samples of malignant breast neoplasms were evaluated, of which 731 (47.2%) were diagnosed with simple carcinoma, 542 (35%) with mixed tumor carcinoma, 105 (6.8%) with other histological types and 171 (11%) carcinosarcomas. There was a higher frequency of mixed-breed, elderly and non-neutered animals. Statistical analysis was performed using the Kruskal-Wallis and Mann-Whitney tests, which revealed a significant association between the variable tumor size in relation to race (p = 0.000), contraceptive administration (p = 0.001), degree of malignancy (p = 0.000) and histological types (p = 0.000). In the race category, the results suggest that Labradors had larger diameter tumors compared to the others. As for the histological parameters, the ones with the highest proportions were tumors classified as carcinosarcomas and grade III malignancy. Furthermore, the use of contraceptive drugs was also shown to be a factor related to the larger size of the nodules.